Solitons, stability analysis and modulation instability for the third order generalized nonlinear Schrodinger model in ultraspeed fibers - Badshah, Fazal; Tariq, Kalim U.; İnç, Mustafa; Kazmi, S. M. Raza (Springer, 2023)
In optical fiber theory, the nonlinear Schrodinger equation (NLSE) is one of the most important physical models for describing the transmission of optical soliton growth. Due to the large range of possibilities for superfast signal processing and light pulses in communications, the wave propagation in nonlinear fibers is currently a topic of substantial curiosity. In this study, the third order generalized NLSE is investigated analytically by using the extended hyperbolic function technique, the improved F-expansion method, and the Adomian decomposition method, which has great importance in applied physics especially in the study optical fibers. The obtained solutions are newly made also they have the form of optical solitons, singular bell shaped, multi-bell shaped, and singular periodic solitons wave behavior and have applications in the optical fibers transmission, physics and many other scientific fields. The stability along with the modulation instability (MI) of the governing model has also been examined to validate the results. The nonlinear model properties have been illustrated using 3D, 2D, and contour plots with the appropriate set of parameters, which is demonstrated to visualize the physical structures more productively. Finally, it is concluded that similar strategies can also be implemented to study many contemporary models.
Keywords: Solitons; Wave solutions; Third order generalized nonlinear Schrodinger equations; Semi-analytical solutions; Stability analysis; MI